Delivery Systems of Trichoderma Inoculants for the Control of Rhizoctonia Diseases in Brassica Rapa - Mohamed Daghman, Ibrahim (2005)
Trichoderma spp were tested as a biocontrol agent against Rhizoctonia solani Kuhn on Brassica rapa. R. solani was isolated from infected vegetables and confirmed the pathogenic to three cultivars of Brassica causing pre-and post emergence damping-off. Confrontation assay, based on the inhibition of mycelial growth and colony overgrowth, showed different degrees of antagonism by Trichoderma isolates to R. solani through competition and mycoparasitism. Two primers (OPC-11 and OPC-15), and RAPD-PCR analysis were used to establish the variability between the nine Trichoderma isolates. The results of which were used to construct a Dendogram. OPC-11 generated 19 RAPD fragments ranging from 200 bp to 3000 bp and OPC-15 generated 18 RAPD fragments ranging from 300 bp to 4000 bp. They successfully grouped the Trichoderma isolates into two main clusters as species aggregates viz. T. harzianum and T. virens. The DNA polymorphism confirmed the identification based on cultural and morphological characteristic. Two of the isolates T. harzanium (UPM40) and T. virens (TV3) were found to establish well on and colonize the roots and rhizospheres of B. rapa. The mixture substrate rice flour and molasses (1:4 RF: ML w/v), incubated three days under shaked culture (100 rpm), was the best for the inoculum production of both Trichoderma isolates. It produced the most conidia (30 x 106 and 22.13 x 106 conidia / g dry mycelium) and mycelium (42.65 mg and 43.97 mg dry mycelium) for UPM40 and TV3, respectively, after only three days incubation. The biomass production was highest at 30 oC incubation temperature for both isolates. Further, desiccation for four days at this temperature still produced good spore viability. UPM40 incorporated on oil palm trunk and chicken dung (OPTCD) and stored at 28 oC and 20 % MC had a significantly longer (P ≤ 0.05) shelf life than other treatments. The shelf lives of the liquid antagonist preparations (UPM40 and TV3) on two food bases and carriers (distilled water and ¼ strength 1:4 RF: ML medium) kept at 10 oC and 28 oC were also evaluated. UPM40 incorporated in the ¼ strength medium and kept at 28 oC had a significantly longer shelf-life (P ≤ 0.05). The dry and liquid formulations of UPM40 could reduce the population of viable R. solani colonies in the infested soil. Both the applications were as effective as the fungicide (Brassicol® 200 mg / L) in protecting the B. rapa against Rhizoctonia pre- and post-emergence damping-off. Bio-coating the seeds of Brassica with similarly reduced damping-off by R. solani